Productive Waqf Management Strategy: Business Planning and Risk Management for Economic Sustainability - Diah Oktaviani (ICO EDUSHA, 2024)
Productive waqf management is a strategic effort to enhance the sustainable social and economic impact of waqf. This article discusses strategies for managing productive waqf by integrating business planning and risk management as steps to ensure sustainability and optimize the benefits of waqf for society. Using a literature analysis approach and case studies, this article explores various methods and best practices in creating adaptive business plans for waqf asset management and risk management approaches to minimize potential losses and improve management efficiency. The findings reveal that comprehensive business planning, accompanied by appropriate risk mitigation strategies, can enhance public trust and broaden the socioeconomic impact of productive waqf. The conclusions from this article provide guidance for waqf managers, Islamic financial institutions, and related stakeholders in implementing effective and sustainable waqf management strategies. Keywords: productive waqf, business planning, risk management, economic sustainability, waqf management, waqf strategy